In Situ Microwave‐Assisted Fabrication of Hierarchically Arranged Metal Sulfide Counter Electrodes to Boost Stability and Efficiency of Quantum Dot‐Sensitized Solar Cells. Issue 5 (4th January 2019) - Tsai, Jia‐Shan; Dehvari, Khalilalrahman; Ho, Wei‐Chuan; Waki, Keiko; Chang, Jia‐Yaw
Abstract: This study describes preparation of metal sulfide counter electrodes (CEs) through one‐pot microwave‐assisted route to improve power conversion efficiency (PCE) of quantum dot‐sensitized solar cells at a lower cost. The CuS nanorods, Ni0.96 S nanoparticles, and PbS nanocubes are synthesized and deposited in situ on fluorine‐doped tin oxide substrate to serve as CEs without further post‐treatment. Effects of several reaction parameters including sulfur precursor (Na2 S, C2 H5 NS, CH4 N2 S), Cu concentration, reaction time, and choice of cation (Cu, Ni, Pb) on the CEs morphology, electrochemical characteristics, and PCE are studied. Furthermore, nanostructure formation and thin film growth are studied and correlated with PCE, from which morphology‐ and composition‐performance relationships can be inferred. Hierarchically assembled nanorod CuS CEs exhibit higher electrochemical stability in the S 2– /S n 2– redox reaction. Together with the efficient charge transfer and higher diffusion coefficient of polysulfide redox at the electrode/electrolyte interface, deduced from electrochemical impedance spectroscopy and Tafel analyses, a PCE of 8.32% is achieved for the CuS CE. The enhanced photovoltaic performance is ascribed to the 1D CuS nanorods forming a diffusive structure which decreases charge transfer impedance and facilitates regeneration of polysulfide redox leading to a higher short‐circuit current density and fill factor. Abstract : Hierarchically assembled metal sulfide thin films are prepared via an in situ microwave‐assisted strategy to serve as counter electrodes for quantum dot‐sensitized solar cells. The correlation between structural and electrochemical characteristics is studied. The improved efficiency of copper sulfide hierarchical structure is assigned to minor charge transfer impedance and higher diffusion coefficient leading to enhanced current density and fill factor.